Evaluating the Effects of Environmental Factors on the Adoption of HR Analytics in Nepalese Organizations - Chhetri, Shanti Devi; Gupta, Chander Mohan (Journal of Business and Management, 2024)
Background: Human resource (HR) analytics has drawn important interest from organizations since it assists companies in managing and sharing data more flexibly and economically and enables scalable business operations by providing flexible storage solutions. However, organizations in Nepal face many issues that influence the acceptance of HR analytics.Objectives: The goal of this study is to find out the impact of environmental factors on HR analytics adoption in Nepalese organizations.Methods: Based on a quantitative approach and using a self-administered questionnaire with 205 responses from various types of organizations were selected through purposive sampling techniques for data collection. Descriptive and inferential statistical techniques were applied to analyze the data using SPSS AMOS.Results: The results indicate that employee orientation and trading partner pressure are the elements that affect HR analytics adoption in Nepalese organizations. While external pressure does not have any effect on the usage of HR analytics.Conclusion: The findings show that it is important to train and make employees aware of HR analytics for easy adaptability. The organization should emphasize educating employees on data analytics. Also, the trading partner pressure plays a critical role, it is important to collaborate with trading partners to encourage the adoption of HR analytics. Since external pressure does not impact, it is not necessary to rely on competitors for the adoption of analytics. The results of this study are especially noteworthy since they highlight the enormous difficulties the organization experiences in trying to modify management practices while also adding to our understanding of management theory and the adoption of technology.JEL Classification: O15, C30